Analisis Pengembangan Produk Abon Ikan Kabupaten Pangandaran: (Studi Kasus: Rumah Produksi Mahakarya “Canting”) - Junianto Junianto; Keysa Alia Zatifa; Atik Nurhasanah; Zulfiqor Meetrand (Jurnal Riset Akuntansi, 2024)
Fluctuations in sales volume can affect profits and add challenges for manufacturers in facing competition. Product development is a key strategy to improve competitiveness and meet consumer expectations through offering quality products. This study aims to analyze the development of shredded fish products at Mahakarya Canting Production House, Pangandaran. The research method used was a survey to select the business as the research location. The results show that Mahakarya Canting Production House has carried out product development through several aspects such as the existence of variations in raw materials, recipe adjustments, production processes, packaging design, packaging size and marketing strategies. A successful transition from traditional methods to modern production techniques can improve the efficiency and quality of the shredded fish products produced. In addition, innovative packaging design significantly increases the appeal of the product, especially among children. This research shows that Mahakarya Canting's strategy can serve as a model for other MSMEs looking to improve product offerings and market reach.